Plasma nitrate concentration in infective gastroenteritis and inflammatory bowel disease. Issue 3 (September 1996) - Dykhuizen, R S; Masson, J; McKnight, G; Mowat, A N; Smith, C C; Smith, L M; Benjamin, N
Abstract : BACKGROUND: In subjects on a low nitrate diet, plasma nitrate concentration and urinary nitrate excretion are thought to reflect endogenous nitric oxide (NO) production, and have been reported to increase during infective and inflammatory bowel disease. AIMS: To compare the extent of NO production in patients with infective versus non-infective forms of bowel dysfunction. SUBJECTS: Four groups: 20 healthy, volunteer clerical and laboratory staff, 12 patients with irritable bowel syndrome, 19 patients with inflammatory bowel disease, and 20 patients with infective gastroenteritis. METHODS: The plasma nitrate concentration was determined with a copper coated cadmium column and spectrophotometry. Mean and median plasma nitrate concentrations were calculated and compared within the four groups. Mann-Whitney distribution free rank testing was used to compare the median values. RESULTS: Median plasma nitrate concentrations in the four groups were: controls 32.7 mumol/l; irritable bowel syndrome 35.5 mumol/l; inflammatory bowel disease 35.1 mumol/l; and gastroenteritis 117.9 mumol/l (p < 0.001 gastroenteritis v all other groups). CONCLUSIONS: Plasma nitrate concentration could serve as a discriminant between infective and inflammatory or functional bowel disease in patients presenting with diarrhoea. It is not clear why there is considerable difference in endogenous nitrate synthesis in these two conditions, which are both characterised by severe gut inflammation.